Eternal and Evanescent Black Holes: It’s All Done With Mirrors - Good, Michael R.R.; Linder, Eric V. (NURIS; Energetic Cosmos Laboratory, 2017)
The analogy between black hole radiation and accelerating mirror radiation (the dynamical Casimir effect) is particularly strong for mirror trajectories giving rise to a constant thermal flux of particles. We present new ways to achieve such thermal plateaus, and customize their finite, semi-infinite, and eternal presence, corresponding to forming/collapsing, complete-evaporation/remnants,and eternal black holes. We find simple expressions for the energy flux in terms of the mirror rapidity as a function of proper time and null time.
Energetic Cosmos Laboratory. ECL Publications
Keywords: The 2nd international conference of the Energetic Cosmos Laboratory (ECL); ECL19; Energetic Cosmos Laboratory (ECL)